2005
DOI: 10.1021/jm050815o
|View full text |Cite
|
Sign up to set email alerts
|

SAR by MS:  Discovery of a New Class of RNA-Binding Small Molecules for the Hepatitis C Virus:  Internal Ribosome Entry Site IIA Subdomain

Abstract: A new class of small molecules that bind the HCV RNA IRES IIA subdomain with sub-micromolar affinity is reported. The benzimidazole 'hit' 1 with a KD approximately 100 microM to a 29-mer RNA model of Domain IIA was identified from a 180000-member library using mass spectrometry-based screening methods. Further MS-assisted SAR (structure-activity relationships) studies afforded benzimidazole derivatives with sub-micromolar binding affinity for the IIA RNA construct. The optimized benzimidazoles demonstrated act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
184
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(197 citation statements)
references
References 26 publications
(47 reference statements)
12
184
0
1
Order By: Relevance
“…It is noteworthy that the pathway of IFN inhibition of viral replication occurs via an IRES-dependent mechanism (11). Both the IRES structure and the mechanism of HCV translation initiation (e.g., 12, 13) have been the subject of intense research in recent years as a therapeutic target (14)(15)(16)(17). As an example, the synthetic steroid mifepristone specifically inhibits in vitro translation initiation from the HCV IRES (18).…”
mentioning
confidence: 99%
“…It is noteworthy that the pathway of IFN inhibition of viral replication occurs via an IRES-dependent mechanism (11). Both the IRES structure and the mechanism of HCV translation initiation (e.g., 12, 13) have been the subject of intense research in recent years as a therapeutic target (14)(15)(16)(17). As an example, the synthetic steroid mifepristone specifically inhibits in vitro translation initiation from the HCV IRES (18).…”
mentioning
confidence: 99%
“…Recent cryo-EM studies confirm the conformational flexibility of domain II through comparison of 40S-bound binary and 80S-bound initiation complexes of the HCV IRES (14). Motivated by the discovery of a riboswitch-like binding site for benzimidazole translation inhibitors (19) in the extended form of subdomain IIa (21), we hypothesized that a cognate ligand may serve as the biological actuator of the RNA switch that ultimately facilitates ribosomal release from the IRES. Inspection of the crystal structure previously determined for an inhibitor complex of subdomain IIa suggested that benzimidazole derivatives might be fortuitous ligands that exploit a recognition site for guanine.…”
Section: Discussionmentioning
confidence: 99%
“…1D) that bind to the internal loop and block translation by capturing distinct conformational states of the RNA (7). Structure analysis revealed that benzimidazole inhibitors such as compound 1 (19,20) interact with an extended architecture of IIa in which the stems flanking the internal loop are coaxially stacked on both sides of the ligand-binding pocket ( Fig. 1E) (21).…”
mentioning
confidence: 99%
“…Isis-11 was prepared as a mixture of enantiomers according to a previously published procedure with minor modifications. 33 The identity and purity of all the compounds were confirmed by mass spectrometry as well as 1 H-and 13 C-NMR spectroscopy. Full experimental details can be provided upon request.…”
Section: Methodsmentioning
confidence: 97%
“…29 In the IRES context, 2-aminobenzimidazole derivatives have also been shown to interact with the SLIIa structural element of the HCV-like IRES, 30,31 and to interfere with viral multiplication at low micromolar concentrations. 32,33 However, to the best of our knowledge, their potential to bind other types of IRES elements as well as cap-dependent translation has not been examined.…”
Section: Introductionmentioning
confidence: 99%